Pulmonary Edema and Hemorrhage due to Heroin Use - Köse, Ataman; Dündar, Gül; Ayrık, Cüneyt; Bozkurt, Seyran; Bingöl, Özlem (The Bulletin of Legal Medicine, 2014)
Numerous reasons may cause pulmonary hemorrhage. Drug induced intoxications, mostly caused by anticoagulants, cocaine and opiates are not frequent causes of pulmonary haemorrage. We present a case of a 24 year-old boy, who admitted to our emergency department with pulmonary hemorrhage, respiratory distress and unconsciousness. He was a heroin addict. The patient’s initial presentation resulted in the consideration of a broad differential diagnosis for his symptoms. He was immediately intubated, taken to the intensive care unit with the diagnosis of pulmonary edema and started to be ventilated mechanically. The patient was was discharged a week after admission. Toxic agents use (heroin, cocain etc.) should be taken into consideration in differential diagnosis of young patients presenting with non-cardiogenic pulmonary edema and hemoptysisKey words: Heroin, Pulmonary edema, Hemorrhage, Respiratory distress
Keywords: heroin; pulmonary edema; hemorrhage; respiratory distress